1994
DOI: 10.1139/x94-035
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of snowshoe hare feeding preferences to nutrient and tannin content of four conifers

Abstract: The relative preferences of snowshoe hares for native and exotic tree species and the relationship of these preferences to nutritional constituents and phenols have important forestry management implications. Thus, feeding preferences of confined snowshoe hares (Lepusamericanus Erxleben) for Siberian larch (Larixsibericus (Endl.) Sabine ex Trautv.), Norway spruce (Piceaabies (L.) Karst.), white spruce (Piceaglauca (Moench) Voss), and black spruce (Piceamariana (Mill.) B.S.R) were examined under two experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The concentrations of salicin and condensed tannins had a strong and negative correlation with vole feeding (Tables 1, 2; Bucyanayandi and Bergeron 1990, but see Rangen et al 1994;Rousi 1989). In particular, the negative correlation between the concentrations of salicylates and vole feeding was strong within the tasted and clearly browsed twigs Fig.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The concentrations of salicin and condensed tannins had a strong and negative correlation with vole feeding (Tables 1, 2; Bucyanayandi and Bergeron 1990, but see Rangen et al 1994;Rousi 1989). In particular, the negative correlation between the concentrations of salicylates and vole feeding was strong within the tasted and clearly browsed twigs Fig.…”
mentioning
confidence: 94%
“…Vole feeding may be critical in short-rotation cultivation of herbal willow, a willow that has a high concentration of salicylates in its bark and leaves, and is therefore cultivated for use as raw material for herbal medicine. Of the small mammals feeding on willows, voles and hares have been shown to prefer food plants with a high content of nitrogen and low contents of total phenolics and terpenoids (Hjältén andPalo 1992, Laitinen et al 2003; but see Rousi, 1989;Rangen et al 1994). Their food selection is also known to vary depending on plant genetics, environment and ontogeny (Bryant 1981;Laitinen et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Diet selection studies have demonstrated that hares preferentially browse deciduous species, but may rely on conifers during winter or during periods of high population density if preferred forage is not available (Aldous and Aldous 1944;de Vos 1964;Parker 1984). Snowshoe Hares often avoid White Spruce (Picea glauca) when other browse is available, presumably because of high levels of camphor in the foliage (Sinclair et al 1988;Rangen et al 1994;Heinen and Currey 2000). The concentration of secondary compounds in vegetation may also influence diet selection (Fox and Bryant 1984;Rousi 1997;Rodgers and Sinclair 1997).…”
mentioning
confidence: 99%
“…Mammalian plant avoidance has been correlated with tannin content for many species (Robbins et al, 1987;Clausen et al, 1990;Roy and Bergeron, 1990;Sunnerheim-Sjoberg and Hamalainen, 1992;Rangen et al, 1994;McMahon et al, 2000). Tannins reduce forage digestibility in ruminants and can cause ulcers in the gastrointestinal tract (Dawson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%